PENGARUH PRAKTIK KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PESERTA DIDIK KELAS XII PEMASARAN SMKN 8 PONTIANAK - Maimuna, Maimuna; Syahrudin, Husni; Kuswanti, Heni (Universitas Tanjungpura, 2023)
The goals of this research are to determine: 1) the prevalence of entrepreneurial practices in the business centers of class XII students majoring in marketing at SMK Negeri 8 Pontianak; 2) the level of entrepreneurial interest among these students; and 3) the extent to which exposure to entrepreneurial practices influences students' interest in entrepreneurship. The strategy employs a quantitative methodology based on correlation. A representative sample of the entire student body (n=94) was taken. Linear regression is used as the method for analyzing the data. According to the findings, 1) a large majority (74.40%) of class XII marketing majors have a favorable view of entrepreneurial practices. 2) Class XII students who plan to study marketing fall into the